Synthesis of quinoline-based NNN-pincer nickel(II) complexes: a robust and improved catalyst system for C–H bond alkylation of azoles with alkyl halides - Patel, Ulhas N.; Pandey, Dilip K.; Gonnade, Rajesh G.; Punji, Benudhar (Organometallics, 2016)
The quinoline-based pincer nickel(II) complexes κN,κN,κN-{R2N-C6H4-(μ-N)-C9H6N}NiX ((R2NNNQ)NiCl: R = Me, 2a; R = Et, 2b) were synthesized by the reaction of the ligand precursors (R2NNNQ)H (R = Me, 1a; R = Et, 1b) with (DME)NiCl2 in the presence of Et3N. Similarly, the pincer nickel(II) derivatives (R2NNNQ)NiX (R = Me, X = Br, 3a; R = Et, X = Br, 3b; R = Me, X = OAc, 4a) were obtained by treatment of the ligands (R2NNNQ)H with the nickel precursor (THF)2NiBr2 or Ni(OAc)2. All of these complexes were characterized by 1H and 13C NMR spectroscopy as well as by elemental analysis. Further, the molecular structures of 2a and 3a,b were elucidated by X-ray crystallography. Complex 2a is found to be an efficient catalyst for the direct C–H bond alkylation of substituted benzothiazoles and oxazoles with various unactivated alkyl halides containing β-hydrogens under mild reaction conditions. The catalyst 2a is very robust and was recycled and reused five times for the alkylation reaction without a decrease in its catalytic activity. Preliminary studies reveal that the catalyst 2a acts as an active catalyst and the alkylation reaction appears to operate via a radical pathway.